AKUNTANSI SEKTOR PUBLIK UNTUK MENCEGAH FRAUD PADA SEKTOR PUBLIK DI ERA DIGITAL - Angel Novita Putri; Retnosari Retnosari (Politeknik Negeri Ambon, 2023)
Government agencies are guided by the public sector accounting recording method which contains the accounts used in recording the operations of government agencies. High-level state entities and agencies, which include municipalities, agencies, major parties, and many other non-profit organizations, are covered by public sector accounting. Public sector accounting is closely related to the digital era because it will be used for the publication of financial reports. The purpose of this study is to see the impact of public sector accounting as a means of fraud prevention in the public sector in the digital era. This study used a qualitative approach using descriptive techniques to explain the results of the study. The results of the research produced are that public sector accounting has a close relationship with fraud prevention. in other words, through a positive attitude that is applied to the existence of digitalization, it will determine a device as a problem or responsibility that can be used as a form of increasing identity